Efektifitas Pengelolaan Air dan Tanah dalam Meningkatkan Hasil Produksi Pertanian di Desa Sampali Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang, Sumatera Utara - Rifani Olivia Nainggolan; Oka Nelli Hutagoal; Febiyola Dasuha; Muhammad Rizky; Sahala Fransiskus Marbun (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the effectiveness of natural resource management, particularly water and soil, in increasing agricultural production in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency. The research approach used was descriptive qualitative through field observations, in-depth interviews with farmers and village officials, and documentation studies from relevant agencies. The results indicate that the irrigation system in Sampali Village is not operating effectively, characterized by shallowing of canals, damaged irrigation walls, and blockages that cause uneven water distribution. This condition has a significant impact on crop yields, with a difference in production between upstream and downstream areas reaching 1.9 tons/ha. Furthermore, soil quality has also declined due to the excessive use of chemical fertilizers, as indicated by a soil pH that tends to be acidic (5.4–6.0), low organic matter content (1.2–1.8%), and decreased soil biological activity. Factors influencing the effectiveness of water and soil management include technical, environmental, socio-economic, and institutional aspects. This study concludes that natural resource management in Sampali Village is still suboptimal, necessitating improvements to irrigation infrastructure, increased use of organic fertilizers, and institutional strengthening and farmer mentoring. These efforts are expected to support sustainable agricultural productivity gains.